Evaluation of Mackerel scad Fishery Management in Ternate Island Waters Based on EAFM in the Domain of Resources and Fishing Techniques - Arianto, Muhammad; Tangke, Umar; Titaheluw, Syahnul Sardi; Masiyah, Siti (Agrikan Jurnal Agribisnis Perikanan, 2022)
This research was carried out in March 2021, in Sasa Village, Ternate City, South Ternate District. North Maluku Province. Data Analysis To be able to answer the purpose of this study, an analysis of the data obtained was carried out and then interpreted the data. Data analysis was carried out in stages starting from the analysis of the fish resource domain, namely the CPUE study, fish size, proportion of scad caught, species composition, "Range Collapse"/(fishing ground) of fish resources and ETP Species (which are protected. Analysis later continued to get the composite value of the fish resource domain, where the results of the scale conversion value are displayed in the form of a flag model. The results of the analysis of the composite value in the fish resource domain obtained a value of 88, so it can be seen that for the fish resource domain the level of management is still in good condition. â€œExcellentâ€ with phage mode â€œDARK GREEN.â€ In the processing of of Mackerel scad in island waters, it is classified as very good.